2003
DOI: 10.1093/treephys/23.18.1247
|View full text |Cite
|
Sign up to set email alerts
|

Developmental stages during the rooting of in-vitro-cultured Quercus robur shoots from material of juvenile and mature origin

Abstract: In-vitro-cultured shoots of clones initiated from shoots of the basal parts (BS) and the crown (C) of two mature Quercus robur L. trees were subjected to rooting experiments to relate rooting with shoot topophysical origin. The BS shoots exhibited morphologically juvenile characteristics and rooted more easily after indole-3-butyric acid (IBA) treatment than C shoots. When naphthylphthalamic acid (NPA) was applied to BS shoots, rooting capacity decreased and root emergence was delayed at least 2 days compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
54
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(63 citation statements)
references
References 34 publications
9
54
0
Order By: Relevance
“…In the present study, we also confirmed IAA concentration (87.3 pmol/g fw) in Q. serrata roots was comparable with that of rice (82.1 pmol/g fw) [18]. IAA concentration in in vitro cultured shoots of Q. robur was about 300 to 700 nmol/g dry weight (dw) in basal area and about 10 to 70 nmol/g dw in apical section [20]. IAA concentration in roots of Q. serrata was about 82 to 88 pmol/g fw in the present study, so the IAA concentration in Q. serrata roots was very low compared with that of Q. robur shoots.…”
Section: Discussionsupporting
confidence: 86%
“…In the present study, we also confirmed IAA concentration (87.3 pmol/g fw) in Q. serrata roots was comparable with that of rice (82.1 pmol/g fw) [18]. IAA concentration in in vitro cultured shoots of Q. robur was about 300 to 700 nmol/g dry weight (dw) in basal area and about 10 to 70 nmol/g dw in apical section [20]. IAA concentration in roots of Q. serrata was about 82 to 88 pmol/g fw in the present study, so the IAA concentration in Q. serrata roots was very low compared with that of Q. robur shoots.…”
Section: Discussionsupporting
confidence: 86%
“…Histological studies using woody species Castanea sativa and Quercus sp. showed that the exogenous application of auxin reactivates cell proliferation but not the formation of new root meristems in mature explants (Ballester et al, 1999;Vidal et al, 2003). A recent study using Pisum sativa suggested that the vegetative-to-reproductive transition is linked to the reduced root regenerative capacity and that this is caused by the loss of auxin responsiveness in reproductive shoots (Rasmussen et al, 2015).…”
Section: Developmental Constraints That Impact Plant Regenerationmentioning
confidence: 99%
“…This indicates development of vein density during the rooting stages. Auxin treatment at rooting stage promotes mitotic dedifferentiation and development of secondary vascular tissues, cambial cells and inter-fascicular supporting tissues (Vidal et al 2003). Vein density was gradually increased via an ex vitro rooting mechanism.…”
Section: Discussionmentioning
confidence: 99%